Mechanisms of bradycardia in premature infants: Aerodigestive–cardiac regulatory–rhythm interactions. Issue 13 (8th July 2020) - Hasenstab‐Kenney, Kathryn A.; Bellodas Sanchez, Jenny; Prabhakar, Varsha; Lang, Ivan M.; Shaker, Reza; Jadcherla, Sudarshan R.
Abstract: Objective: Eating difficulties coupled with cardiorespiratory spells delay acquisition of feeding milestones in convalescing neonates, and the mechanisms are unclear. Aims were to examine and compare the pharyngoesophageal–cardiorespiratory (PECR) response characteristics: (a) in control neonates and those with recurrent bradycardia spells; and (b) during pharyngeal stimulation when bradycardia occurs versus when no bradycardia occurs. Methods: Preterm infants ( N  = 40, 27 ± 3 weeks gestation), underwent concurrent pharyngoesophageal manometry, electrocardiography, respiratory inductance plethysmography, and nasal airflow thermistor to evaluate pharyngoesophageal motility, heart rate (HR), and respiration during graded abrupt pharyngeal sterile water stimuli. Infants with recurrent bradycardia ( N  = 28) and controls ( N  = 12) were evaluated at 38 (38–40) and 39 (38–40) weeks postmenstrual age, respectively. Comparisons were performed (a) between study and control groups; and (b) among HR responses of <80 BPM, 80–100 BPM, and >100 BPM. Results: Overall, characteristics of PECR responses in infants with a history of recurrent bradycardia (vs. controls) did not differ ( p  > .05). However, when pharyngeal stimulus induced severe bradycardia (<80 BPM): prolonged respiratory rhythm change, increased pharyngeal activity, increased esophageal dysmotility (as evidenced by prolonged esophageal inhibition and motor activity), and prolonged lower esophageal sphincter relaxation were noted (all p  < .05). Conclusions: In control infants and those with recurrent bradycardia, pharyngeal stimulation results in similar PECR response characteristics. However, when severe bradycardia occurs, PECR response characteristics are distinct. The mechanisms of severe bradycardia spells are related to abnormal prolongation of vagal inhibitory effects on cardiorespiratory rhythms in conjunction with prolonged esophageal inhibition and delays with terminal swallow. Abstract : Pharyngeal stimulation shows that pharyngeal‐esophageal‐cardiac‐respiratory (PECR) response characteristics are not different in infants with recurrent bradycardia. However, PECR dysfunction occurs during severe bradycardia and its mechanisms are related to abnormal prolongation of vagal inhibitory effects on cardiac‐respiratory rhythms in conjunction with prolonged esophageal inhibition and delays with terminal swallow.